Analisis Persepsi Anggota Koperasi Terhadap Perbaikan Layanan Dari Dampak Penggunaan Sistem Simpan Pinjam Koperasi Divif 1 Kostrad Depok - Elmor Benedict Wagiu; Rianto Doharma Sihotang (TeIKa, 2018)
Business process research that occurs in the Divif 1 Kostrad Cooperative aims to determine the qualityof services provided to the members. The problem that arises is how the impact of service users on thesystem occurs in the Savings and Loan Cooperative and whether it will be influenced by membersperceptions of the quality of the system used right now. 89 sampled respondents are divided into threedivisions using purposive sampling technique with calculation of Slovin formula and data collectionthrough questionnaires. The research objectives are: (1) Knowing how users influence the servicesystem in the Savings and Loan Cooperative on additional functions in the system or renewal of systemsupport tools. (2) Knowing whether perceptions of satisfaction and feasibility perceptions influence theacceptance of members of the Tentara Nasional Indonesia (TNI) Kostrad from the impact of using theSavings and Loan Cooperative System. The author calculates the results of the research usingSugiyono’s quantitative research method formula. The results of the research from the questionnaireindicate that perceptions of satisfaction and perceptions of feasibility influence the impact of using theSavings and Loan Cooperative System.Keywords: purposive sampling, quantitative research, SPSS, savings and loan cooperatives